قرآن کا سائنسی اُسلوبِ تفسیر اور اس کی اہمیت و افادیت : ایک تحقیقی مطالعہ: Scientific Method of Quranic Interpretation and Its Significance and Benefits: A Research Study - Dr Irfan Jafar; Muhammad Saad Dehlvi; Asia Parveen (AL-IDRAK JOURNAL, 2024)
The Qur'an serves as a comprehensive source encompassing diverse scientific knowledge, detailing celestial, terrestrial, and historical phenomena. It describes unique creatures and cosmic events, alongside the origins of creation and the lives of prophets and angels. These concepts, presented in the Qur'an, have remained unchallenged by scientific inquiry to date. Islam, through its emphasis on knowledge and inquiry, has historically contributed to the elevation of science in society, albeit not as the initial promoter. Scientific commentary on the Qur'an aims primarily to facilitate understanding rather than to advance scientific progress alone, though it inevitably contributes to new areas of exploration. This approach appeals to individuals seeking empirical insights into the Qur'an's teachings, prompting discussions on its contemporary relevance and societal impacts. Modern generations, grappling with complex issues and influenced by secular perspectives, increasingly find value in scientific commentary as a means to reconcile faith with contemporary knowledge. This trend has gained traction among Islamic scholars, fostering constructive engagement with scientific discoveries and promoting a deeper understanding of the universe's mysteries.